Political and Diplomatic Networks of Nuruddin Zanki in The Middle East: A Historical Review/ Historiography - Lydia Megawati; Nuraeni; Jusmiati (Pappaseng: International Journal of Islamic Literacy and Society, 2025)
The study seeks to determine the political and diplomatic network of Nuruddin Zanki in the Middle East through a historical/historiographic review. Adopting a historical approach, the study was divided into several methods, including heuristic, critical, and historiography. The findings of this study conclude that Nuruddin Zanki was a prominent Islamic figure who consistently fought in the Second Crusade, as indicated by his success in reclaiming Islamic territory from the hands of the Christians, including the cities of Artah and Harene and other regions. He was also a leader who succeeded in unifying and strengthening Islamic power in the Middle East, particularly in facing the Second Crusade. He strategically administered political and military networks, including unifying Muslim territory, securing borders, and forging alliances with other Islamic forces. Furthermore, he was renowned for his just, firm, and wise characters which were able to inspire his people to fight as one. His Islamic diplomatic initiatives were successful in uniting Muslims and strengthening their resilience, allowing them to withstand the invasion of the crusaders and pave the way for Salahuddin Ayyubi in supporting Jerusalem. Nuruddin Zanki’s Islamic diplomacy was successful in uniting Muslims and strengthening them so that they were able to battle the attacks of the crusaders and paved the way for Salahudin Ayyubi to assist Jerusalem. His focus was not only on battle but also on investing in infrastructure as well as the economic and military development of his region.